NMRP of styrene-divinylbenzene: predictions in the pre- and post-gelation periods using different modelling approaches - Aguiar, Leandro G. (2013)
Three modeling approaches for the NMRP of slyrene-divinylbenzene were used for describing experiments performed at different initial conditions: a rigorous approach (model A) based on balance of species and method of characteristics in terms of generating functions and two simplified approaches based upon mass and moment balances, numerical fractionation and pseudo-kinetic method (models B and C). Balances of paths connecting groups were used for tackling loop formation reactions. A critical comparison of the effect of underlying assumptions of lhe three approaches was carried out. Simulations making use of the concept of path balances presented good results for the predictions of pendant double bonds (PDB) concentration. Numerical fractionation can easily allow for empirical reactivity changes with average molecular size (Through the generation index). Thus, simultaneous agreement for predictions of sol weigh-average molecular weigh (Mw) and gel fraction (Wg) could be found with experiments at 90º C. Experiments at 130 º C implied a higher crosslinking reactivity. which might be related lo a higher mobility of polymer chains.